Bystander CPR – EuReCa_ Serbia 2014 -2019 - Lazić, Aleksandra; Sasa, Sasa; Fiser, Zoran (Journal Resuscitatio Balcanica, 2020)
ABSTRACT The aim of this study is to determinate a chance of surviving in bystander CPR in out-of-hospital cardiac arrest (OHCA) in Serbia. Methodology: The study was conducted as a prospective and observational study of the collection of data in the period 2014 -2019 via the National OHCA Registry Serbia. EuReCa program is registered Clinical Trial ID:NCT03130088. Data analysis was done by IBM SPSS Statistics 20. Results: A total of 6312 OHCA is registered. A witness was present in 3655/6312 or 57,9% OHCA, but CPR is done in 365/3655, or 10,2% witness presented OHCA. ROSC is achieved in 9,7% patients, 6,6% patients which CPR by bystander were not done and 28,1% patients in which CPR by bystander were done, which is statistically significant (χ2 = 122,792; df = 1; p = 0.000). A chance for ROSC is 5,4 higher when CPR by bystander is done before EMS arrival (OR = 5,4; 95% C.I. 3,967-7.377). ROSC has commonly occurred in older males with shorter EMS time to arrival but most important is bystander CPR. Conclusion: People who experienced out-of-hospital cardiac arrest have a 5,4 higher chance for ROSC which means, finally observing, a higher chance for survival when bystander CPR is performed.